Effect of nitrogen levels on pattern of incremental biomass partitioning in rice (Oryza sativa) at different growth stages - KRISHNAN, P; SWAIN, P; NAYAK, S K (The Indian Journal of Agricultural Sciences, 2013)
A study was conducted during 1994-95 to changes in dry weight with time of each aerial component and new incremental biomass as being partitioned into them in 2 rice (Oryza sativa L.) varieties, tall ’Swarnaprabha’ and medium tall ’IR 36’ at 5 different levels of N, viz 30,60,90,120 and 150 kg N/ha at 10 days interval. Nitrogen levels influenced the growth of all aerial components of the plant as well as the partitioning of dry-matter at different developmental stages. Partitioning of dry-matter of leaves was maximum (0.526) during vegetative stage, while it attained a maximum value of 0.75 for stem during panicle-initiation stage. The N-responsive ’IR 36’ rice having high leaf NÂ uptake (6.06 g N/m2 average of all samplings) had higher partitioning coefficient to leaves (0.53) than that to the stem (0.47) and the converse was true with low-N responsive ’Swarnaprabha’ rice.